A Supernumerary Soft Robotic Limb for Reducing Hand-Arm Vibration Syndromes Risks - Ciullo, Andrea S.; Catalano, Manuel G.; Bicchi, Antonio; Ajoudani, Arash (Frontiers in Robotics and AI, 2021)
The most common causes of the risk of work-related musculoskeletal disorders (WMSD) have been identified as joint overloading, bad postures, and vibrations. In the last two decades, various solutions ranging from human-robot collaborative systems to robotic exoskeletons have been proposed to mitigate them. More recently, a new approach has been proposed with a high potential in this direction: the supernumerary robotic limbs (SRLs). SRLs are additional robotic body parts (e.g. fingers, legs, and arms) which can be worn by the workers, augmenting their natural ability and reducing the risks of injuries. These systems are generally proposed in the literature for their potentiality of augmenting the user's ability, but here we would like to explore this kind of technology as a new generation of (personal) protective equipment. A supernumerary robotic upper limb, for example, allows for indirectly interacting with hazardous objects like chemical products or vibrating tools. In particular, in this work, we present an SRL system with the aim to reduce the vibration transmitted along the arms and minimize the load on the upper limb joints. For this purpose, an off-the-shelf wearable gravity compensation system is integrated with a soft robotic hand and a custom damping wrist, designed starting from theoretical considerations on a mass-spring-damper model. The real efficacy of the system was experimentally tested within a simulated industrial work environment, where seven subjects performed a drilling task on two different materials. Experimental analysis was conducted according to the ISO-5349. Results showed a reduction from 40% to 60% of vibration transmission with respect to the traditional hand drilling, by using the presented SRL system, without compromising the time performance.